1985
DOI: 10.1080/02643298508252864
|View full text |Cite
|
Sign up to set email alerts
|

The effects of minor closed head injury upon human memory: Further evidence on the role of mental imagery

Abstract: 1985) The effects of minor closed head injury upon human memory: Further evidence on the role of mental imagery, Cognitive Neuropsychology, 2:2, 149-168,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…Individual differences in KHMT performance may reflect not only individual differences in verbal memory capacities, if verbal labels are recalled in order to correctly reproduce movement sequences, but also the extent to which there is spontaneous use of verbal strategies to aid movement sequence recall. Richardson and Barry (1985) reported that memory problems following mild traumatic brain injury might reflect a reduced ability to adopt effective strategies to support memory. Results of the current study are consistent with the possibility that impairments in KHMT performance reflect failure to adopt an effective verbal labelling strategy for hand postures.…”
Section: Discussionmentioning
confidence: 98%
“…Individual differences in KHMT performance may reflect not only individual differences in verbal memory capacities, if verbal labels are recalled in order to correctly reproduce movement sequences, but also the extent to which there is spontaneous use of verbal strategies to aid movement sequence recall. Richardson and Barry (1985) reported that memory problems following mild traumatic brain injury might reflect a reduced ability to adopt effective strategies to support memory. Results of the current study are consistent with the possibility that impairments in KHMT performance reflect failure to adopt an effective verbal labelling strategy for hand postures.…”
Section: Discussionmentioning
confidence: 98%
“…4 Persistent disturbance of memory function is the most common cognitive complaint even in mild TBI, with the most frequent memory impairment being recall of new information. [5][6][7] Following severe TBI, 36% of people have permanent and significant memory impairments. 8,9 McKinlay et al 9 reported memory deficits in 73% of cases 3 months postinjury.…”
mentioning
confidence: 99%
“…The test of memory function was taken from an experimental investigation o f mental imagery reported by Richardson (1974), and subsequently employed in neuropsychological research (Richardson, 1978(Richardson, . 1979; Richardson & Barry, 1985;Richardson & Snape, 1984). Fifty nouns were selected from the norms of Paivio, Yuille & Madigan (1968) which had imagery and concreteness ratings of 6.0 or more, and which had frequency ratings in the count of Thorndike & Lorge (1944) of AA or A.…”
Section: Methodsmentioning
confidence: 99%